Bioremoval of Chromium (Cr+3) using leaves of Myrtus communis - Aliaa A. Alsudany; Fawzi S. Alzubaidi (World Journal of Experimental Biosciences, 2015)
The present study showed that leaves of Myrtus communis have many compounds which can serve as hunting net to heavy metals. The potential to remove Cr+3 from aqueous solutions through bio-sorption using leaves of M. communis as agriculture waste was investigated in batch experiments at (200 mg/l). Wilson-Box as mathematical program was used in order to examine several factors influencing metal adsorption such as pH (4-8), contact time (5 – 240 min) and bio-mass (0.1-10 g). The Best rate of Bioremoval of Chromium (99.1%) of 400 mg/l of Chromium (Cr+3) was found at the following conditions: pH, 7.1; contact time, 190.4 min; bio-mass, 2.2g. While, the lowest rate of bioremoval of Cr+3 (45%) was observed at pH, 6; contact time, 122.5 min and bio-mass, 0.1g. At 200 mg/l of Cr+3, the best Bioremoval was similar to the results of 400mg/l but the lowest bioremoval rate was found at pH, 4.8; contact time, 54.6 min and bio-mass, 2.2g. From these results it can be concluded that the leaves of M. communis have good ability to remove Cr+3 from water because its active compounds, which serves as entrapment positions to heavy metals. Finally, it can be hypothesis that heavy metals just like all pollutants can be easy removed by using green chemistry that gives a simple, safe and inexpensive solution to solve the problem of pollution with heavy metals.
Keywords: Bioremova, Chromium, Myrtus communis, pH.